Evaluation of Patients with COVID-19 Followed Up in Intensive Care Units in the Second Year of the Pandemic: A Multicenter Point Prevalence Study - Gungor, Sinem; Ediboglu, Ozlem; Mocin, Ozlem Yazicioglu; Adiguzel, Nalan; Tuncay, Eylem; Iscanli, Insa Guel Ekiz; Tuzuner, Filiz (Aves, 2024)
OBJECTIVE: A 1 -day point prevalence study was planned to obtain country data by determining the clinical characteristics, follow-up and treatment methods of coronavirus disease 2019 (COVID-19) cases that required intensive care unit (ICU) treatment in the second year of the pandemic. MATERIAL AND METHODS: All patients who were hospitalized in the ICUs due to COVID-19 between March 11, 2022, 08.00 AM, and March 12, 2022, 08.00 AM, were included in the study. Demographic characteristics, intensive care and laboratory data, radiological characteristics, and follow-up results of the patients were recorded. RESULTS: A total of 811 patients from 59 centers were included in the study, 59% of the cases were male, and the mean age was 74 +/- 14 years. At least one comorbid disease was present in 94% of the cases, and hypertension was the most common. When ICU weight scores were examined, Acute Physiology and Chronic Health Evaluation -II: 19 (15-27) and Sequential Organ Failure Assessment: 7 (4-10) were seen. Sepsis was present in 37% (n = 298) of cases. PaO2/FiO2 ratios of the patients were 190 the highest and 150 the lowest and 51% of the cases were followed via invasive mechanical ventilation. On the study day, 73% bilateral involvement was seen on chest x-ray, and ground -glass opacities (52%) were the most common on chest tomography. There was growth in culture in 40% (n = 318) of the cases, and the most common growth was in the tracheal aspirate (42%). CONCLUSION: The clinical course of COVID-19 is variable, and ICU follow-up was required due to advanced age, comorbidity, presence of respiratory symptoms, and widespread radiological involvement. The need for respiratory support and the presence of secondary infection are important issues to be considered in the follow-up. Despite the end of the second year of the pandemic and vaccination, the high severity of the disease as well as the need for follow-up in ICUs has shown that COVID-19 is an important health problem.
Keywords: COVID-19; intensive care; intensive care unit; pandemic; follow-up